Native and mutant 5-lipoxygenase expression in a baculovirus/insect cell system. - Funk, C D (1989)
Human 5-lipoxygenase (EC 1.13.11.34), the key enzyme involved in the transformation of arachidonic acid to the potent biologically active leukotrienes, has been overexpressed in insect cells using a baculovirus expression system. A recombinant baculovirus (3B6) carrying the human 5-lipoxygenase coding sequence downstream of the strong polyhedrin protein promoter was isolated. Approximately 48 hr after infection of Spodoptera frugiperda cells with the recombinant baculovirus, maximal intracellular enzyme activity and protein levels were detected. The recombinant 5-lipoxygenase in 10,000 x g supernatant fractions was able to synthesize large amounts of 5-hydroperoxy-6,8,10,14-icosatetraenoic acid, together with smaller amounts of the nonenzymatic hydrolysis products of leukotriene A4, and exhibited a dependence on Ca2+ and ATP for maximal activity. Immunoblot analysis of supernatant proteins from human leukocytes and recombinant virus-infected cells indicated the presence of indistinguishable approximately 80-kDa bands. However, 5-lipoxygenase protein in recombinant-infected cells was found to be present in amounts 50-200 times that present in leukocytes on a per-cell basis. Histidine-362 and histidine-372, potential iron-atom ligands within a putative iron-binding domain, were changed to serine residues. Recombinant baculoviruses carrying the mutations were isolated and used to infect insect cells. Although infected cells were able to express mutant 5-lipoxygenase protein, enzyme activity was not substantially altered, suggesting the nonessential nature of these histidines in binding iron at the putative ferric catalytic site.